The Mediating Role of Government Support in E-wallet Acceptance Intention in Malaysia - Hashim, Kamarul Faizal; Tan, Felix B; Gutierrez, Jairo A (AIS, 2024)
The aim of this research is to examine the factors that predict e-wallet acceptance intention and especially the mediating role of government support that can lead to better intention to accept this technology in Malaysia. The contribution of this research is to explore the nuanced relationships that can help expand the understanding of e-wallet acceptance intention in Malaysia. Furthermore, this study is among the few that investigates the influence of government support as a mediating construct to predict e-wallet adoption intention. This research in progress also presents the study’s research model and method.